2016 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/p.25770
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Development of Programming Skills Using MATLAB within an Undergraduate Dynamics Course

Abstract: This project introduces a method of teaching undergraduate students MATLAB programming within a typical engineering lecture course, dynamics. This particular course was chosen because its content offers natural connections between engineering and programming concepts. The MATLAB programming instruction and assignments were approached through the context of the dynamics course material. This allowed students to make connections between their typical dynamics course content and the more abstract programming conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…At present, there are few colleges and universities specialized in the course of MATLAB, most of which only integrate the course into some professional courses, and set up MATLAB as a solution to some specific problems of relevant specialities.This phenomenon is especially prominent in engineering [2]. In science specialty, it is common to apply MATLAB to relevant mathematics courses.…”
Section: Problems Faced By Matlab For Undergraduate Studentsmentioning
confidence: 99%
“…At present, there are few colleges and universities specialized in the course of MATLAB, most of which only integrate the course into some professional courses, and set up MATLAB as a solution to some specific problems of relevant specialities.This phenomenon is especially prominent in engineering [2]. In science specialty, it is common to apply MATLAB to relevant mathematics courses.…”
Section: Problems Faced By Matlab For Undergraduate Studentsmentioning
confidence: 99%
“…This type of course typically focuses on details of a specific software or language, functional programming in a procedural or object-oriented paradigm, and the use of conditional statements and loops with basic data structures. A variety of languages are taught in such introductory courses as STEM educators have debated which is the "best" programming language to teach university STEM students [1][2][3][4][5] . Some undergraduate and graduate programs also include one or more courses on numerical methods, primarily aimed at teaching algorithms and error analysis techniques while surveying the appropriate methods to be used on categories of mathematical problems.…”
Section: Introductionmentioning
confidence: 99%
“…In one case, the introduction of regular programming assignments in an aerospace department proved beneficial for students, but they concluded that the students lacked the needed foundation in programming for the project to be successful [8]. Further, integration of MATLAB as a regular exercise in a dynamics course was shown to have an impact on the students learning of programming concepts [9] as well as exposure to more complex problems and the concept of uncertainty [10]. Through incorporating these types of projects, the students are forced to understand the theories presented in the courses at a deeper level in order to implement those ideas in a computer program.…”
Section: Introductionmentioning
confidence: 99%